Zincation and Magnesiation of Functionalized Silylated Cyanohydrins Using TMP-Bases - Castelló-Micó, Alicia; Knochel, Paul (Synthesis, 2018)
Polyfunctional silylated cyanohydrins are readily magnesiated or zincated with TMPMgCl·LiCl or TMP2Zn·2MgCl2·2LiCl leading to the corresponding metallated derivatives. These Mg- or Zn-derivatives react with various electrophiles such as benzylic bromides, allylic bromides, acid chlorides, aldehydes, NCCO2Et, or MeSO2SMe. Subsequently, TBAF-deprotection provides the corresponding keto or 1,2-diketo derivatives.
Keywords: metalation; umpolung; organomagnesium reagents; organozinc reagents; benzylation